Patchwork Capitalism in Central and Eastern Europe – a New Conceptualization - Gardawski, Juliusz; Rapacki, Ryszard (Warsaw Forum of Economic Sociology, 2023)
This paper aims at a new conceptualization of the essence of post-communist capitalism that emerged in most former socialist countries in Central and Eastern Europe, with special emphasis on the eleven states that joined the European Union between 2004 and 2013 (CEE11). Our conceptualization highlights the unique nature and peculiar features of this type of capitalism, resulting from the path-dependent evolution of the socio-economic orders in most countries of the region. On the basis of theoretical and empirical research conducted in the field of new institutional economics, new economic sociology, economic anthropology, comparative political economy and related disciplines, as well as applying Weberian ideal-type method, we argue that the CEE11 countries exhibit incoherence of their institutional architectures or else – they lack the institutional 'fabric' of their socio-economic orders (fundamental rules of the game) which would determine the nature of their 'thread', i.e., organizations and secondary institutions (players). Simultaneously, we also show that this is the outcome of both the centuries-long weaknesses of the national institutional architectures in these countries, two institutional and class structure breakdowns or turning points on their development trajectories that occurred in the 1939–1949 and the 1989/1991 periods respectively, as well as the subsequent, unique process of 'building capitalism without capitalists' in the 1990s. As a result of the interaction of multiple factors, in most of the CEE11 countries a peculiar type of capitalism has emerged, which we have described in terms of an ideal type. Its essence boils down to: (i) the weakness of basic institutions making up their socio-economic order, including the state and the law, as a consequence of their historical legacy and the way it was created by the intelligentsia-based 'breakthrough elite'; (ii) the absence of a dominant form of capital able to impose its own 'fabric' preferences: this was, inter alia, a derivative of unconstrained access of foreign capital, coming from various countries, and the coexistence of various forms of national ownership, none of which has achieved or maintained a strong enough position to impose an institutional structure on the entire economy; (iii) the resultant absence of a dominant economic class (e.g. the national bourgeoisie) interested in the existence of a particular 'fabric', ready to defend it and with sufficient political influence to do so; and (iv) the lack of well-internalized – or deeply socially embedded – cultural values supporting the 'fabric'. These factors combined make patchwork capitalism vulnerable to entropic economic growth (the concept wwe discuss in Section 3 of the article) as, due to low institutional barriers to entry, any new organizations and institutions can join it relatively easily, imposing their own logics on the host institutional architectures – exactly the way a patchwork blanket is made through stitching divergent new patches. Given these peculiarities we argue that patchwork capitalism ought to be conceived as a new, distinct research category in comparative studies on post-communist capitalism. Our intention, however, is not to replace the existing typologies of capitalism in CEE11 countries with a new one; rather, we aim to complement and ameliorate them through pointing to a new, peculiar dimension of capitalism, mostly neglected in the hitherto research. The peculiarity of this dimension consists in its two-form character: it either (i) gives certain types of capitalism a patchwork feature, indicating the relative weakness of the institutional 'fabric' involved and vulnerability to transformation, or (ii) denotes a separate object, i.e., it implies the existence of a self-contained type of capitalism, labeled 'patchwork capitalism'. In the latter situation, a specific socio-economic order converges to the ideal type due to the extreme weakness of its 'fabric'. In the first case, an exemplification may be for example 'patchwork corporatism', i.e., an order in which, despite the relative weakness of its fabric, the institutional architecture concerned resembles a coordinated market economy. In turn, in the second case, the institutional fabric is so ambiguous and volatile that its unequivocal classification in conceptual terms inherent to standard typologies of capitalism becomes a challenge, which often leads researchers to qualify a given socioeconomic order as 'heterogeneity'.